Modeling approaches for assessing device-based measures of energy expenditure in school-based studies of body weight status - Honvoh, Gilson D.; Zoh, Roger S.; Gupta, Anand; Benden, Mark E.; Tekwe, Carmen D. (Frontiers in Applied Mathematics and Statistics, 2024)
Background: Researchers increasingly study how obesity is influenced by school-day physical activity and energy expenditure (EE) patterns among school-aged children by using wearable devices that collect data at frequent intervals and generate complex, high-dimensional data. Although clinicians typically define obesity in children as having an age- and sex-adjusted body mass index (BMI) value in the high percentiles, the relationships between school-based physical activity interventions and BMI are analyzed using traditional linear regression models, which are designed to assess the effects of interventions among children with average BMI, limiting insight regarding the effects of interventions among children categorized as overweight or obese. Methods: We investigate the association between wearable device–based EE measures and age- and sex-adjusted BMI values in data from a cluster-randomized, school-based study. We express and analyze EE levels as both a scalar-valued variable and as a continuous, functional predictor variable. We investigate the relationship between school-day EE (SDEE) and BMI using four models. The FMEM (functional mixed-effects model) and FQMEM (functional quantile mixed-effects model) allow the influence of the time of day at which physical activity is performed to be assessed, which is not possible using the LMEM (linear mixed-effects model) or the QMEM (quantile mixed-effects model). Results: The LMEM and QMEM detected a statistically significant effect of overall mean SDEE on log(BMI) after adjusting for intervention, age, race, and sex. The FMEM and FQMEM provided evidence for statistically significant associations between SDEE and log(BMI) for only a short time interval. The functional regression models allow for additional interpretations of the influence of EE patterns on age- and sex-adjusted BMI, whereas the quantile regression models enable the influence of EE patterns to be assessed across the entire BMI distribution. Conclusion: The FQMEM is recommended when interest lies in assessing how device-monitored SDEE patterns affect children of all body types, as this model is robust and able to assess intervention effects across the full BMI distribution. However, the sample size must be sufficiently large to adequately power determinations of covariate effects across the entire BMI distribution, including the tails.